Variability for salt tolerance in a collection of Panicum coloratum var. makarikariense during early growth stages = Variabilidad en tolerancia a la salinidad en una colección de Panicum coloratum var. makarikariense durante las etapas tempranas de crecimiento - Cardamone, Luisina; Cuatrin, Alejandra; Grunberg, Karina; Tomas, Maria Andrea (CIAT, 2019)
Our aim was to investigate variability for salt tolerance in a collection of Panicum coloratum var. makarikariense of INTA EEA Rafaela, Argentina. Panicum coloratum is a C4 perennial grass to be potentially used to increase forage production in areas affected by abiotic factors which reduce their productivity. We evaluated the response of half-sib families from different accessions to increasing salt concentrations under growth chamber conditions. Germination percentage (GP), GP (% of control) and index of germination decreased with increasing salinity, while mean germination time increased (P˂0.001). After being exposed to saline conditions ungerminated seeds were able to recover in distilled water and many germinated. Salt tolerance was more variable between families within accessions than between accessions in all evaluated variables. At the seedling stage, morphological and physiological variables allowed differentiation among families on the basis of salt tolerance. Molecular characterization by ISSR molecular markers demonstrated variability within parent material and grouped families by accessions. A positive but low correlation between morphological and molecular distances was detected (r = 0.24; P = 0.032). Nonetheless, even after selection, enough molecular variability remained within tolerant families grouped by principal components analysis. In summary, materials of P. coloratum var. makarikariense from INTA EEA Rafaela showed both morphological and genetic variability for salinity tolerance and the contrasting genotypes could be used as parent materials to conduct breeding studies to improve salt tolerance in this species.